Health Needs of People Living with HIV/AIDS: From the Perspective of Policy Makers, Physicians and Consultants, and People Living with HIV/AIDS. - Ghobad Moradi; Minoo Mohraz; Mohammad Mehdi Gouya; Masoumeh Dejman; SeyedAhmad Seyedalinaghi; Sahar Khoshravesh; Hossein Malekafzali Ardakani (Tehran University of Medical Sciences, 2014)
HIV/AIDS has been concentrated among injecting drug users in the country. This study aimed to investigate and identify health and treatment needs of people living with HIV/AIDS in Iran.This qualitative study was conducted in 2012 in Iran. The study groups consisted of experts, practitioners, and consultants working with People Living with HIV/AIDS and their families. Data was collected through Focus Group Discussions and deep interviews. Data were analyzed using content analysis method.The findings of this study included the needs of people living with HIV/AIDS, which were classified in three main categories. The first category was prevention and counseling services with several sub-groups such as education and public and available consultation, distribution of condoms to vulnerable groups, increasing counseling centers in urban areas, providing appropriate psychological and supportive counseling, and family planning services. The second category included diagnostic and treatment services and had several sub-groups such as full retroviral treatment, Tuberculosis treatment and continuing care, providing care and treatment for patients with hepatitis, and providing dental services. The third category included rehabilitation services and had some sub-categories such as home care, social and psychological support, nutritional support, and empowering positive clubs.This study puts emphasis on making plans based on the priorities to meet the needs of people living with HIV/AIDS in Iran.